Assessing the Wider Implementation of the SHARP Principles: Increasing Physical Activity in Primary Physical Education - Emma Powell; Lorayne Angela Woodfield; Alexander James Powell; Alan Michael Nevill (MDPI AG, 2020)
To assess the wider application of the SHARP (Stretching whilst moving, High repetition of skills, Accessibility, Reducing sitting and standing, and Promotion of physical activity) Principles intervention on children’s moderate to vigorous physical activity (MVPA) in physical education (PE), when applied by teachers and coaches. A quasi-experimental intervention was employed in nine primary schools (experimental, n = 6: control, n = 3) including teachers (n = 10), coaches (n = 4), and children (aged 5 to 11 years, n = 84) in the West Midlands, UK. Practitioners applied the SHARP Principles to PE lessons, guided by an innovative behaviour change model. The System for Observing Fitness and Instruction Time (SOFIT) was used to measure children’s MVPA in 111 lessons at pre- (n = 60) and post-intervention (n = 51). Seven interviews were conducted post-intervention to explore practitioners’ perceptions. Two-way ANOVA (Analysis of Variance) revealed that teachers increased children’s MVPA by 27.7%. No statistically significant change in children’s MVPA was observed when taught by the coaches. The qualitative results for teachers were ‘children’s engagement’, a ‘pedagogical paradigm shift’, and ‘relatedness’; and for coaches ‘organisational culture’ and ‘insufficient support and motivation’. The SHARP Principles intervention is the most effective teaching strategy at increasing MVPA in primary PE when taught by school based staff (rather than outsourced coaches), evidencing increases almost double that of any previously published study internationally and demonstrating the capacity to influence educational policy and practice internationally.